Exploring Smart Growth Boundaries of Urban Agglomeration with Land Use Spatial Optimization: A Case Study of Changsha-Zhuzhou-Xiangtan City Group, China - Ma, Shifa; Zhao, Yabo; Tan, Xiaohong (Chinese geographical science, 2020)
Urban agglomeration is the main spatial organization mode used by the Chinese government to promote the policy of new urbanization strategy. Hence, a better understanding of the urban growth boundary (UGB) has profound theoretical and practical significance regarding sustainable urban development. This study devised a raster-based land use spatial optimization (LUSO) framework, and utilized ant colony optimization (ACO) algorithm to delimit the smart growth boundaries of the Changsha-Zhuzhou-Xiangtan city group (CZTCG) in China. The aim of this study is to design a LUSO model to explore an optimal pattern of urban agglomeration for sustainable growth. Multi growth scenario including a single development center, multipolar development and balanced development patterns are generated by the LUSO model for the year of 2050, and the optimum spatial pattern is chosen based on objectives comparison and the present stage of economic and social development in CZTCG. The main results are listed as the following. 1) It is feasible to identify the growth boundaries of the urban agglomeration using the land use spatial optimization model, and the optimal form of the spatial pattern can be defined. 2) With the growth trend of the urban agglomeration gradually spreads from a single center to multi-centers and even small towns, the total optimization target performance gradually increases, which means that the traditional pie-shaped development does not meet the maximum comprehensive benefit of the city group. 3) Subject to the regional social and economic development stage, absolute fair development or simply developing the central city is not conducive to promoting the coordinated development of the urban agglomeration. Gradient equalization and gradual advancement are the best choice for UGB delineation of urban agglomeration. The findings of this study would be useful to identify the UGB in CZTCG for more sustainable urban development in the future.